Aspirin Resistance in Patients with Chronic Coronary Syndrome - A.L.Alyavi; Sh.I.Khodjanova; J.K.Uzokov; Sh.Kadirova (Indian Journal of Forensic Medicine & Toxicology, 2021)
This review summarizes aspirin features, actions and resistance in patients with chronic coronary syndrome. As well, it describes mechanism of the aspirin action and possible ways and causality of the aspirin resistance. In addition, it shows how to assess the efficacy of the aspirin therapy in patients with chronic coronary syndrome.